The Influence of Using Learning Media on the Understanding of Office Administration Education Students at Universitas Negeri Makassar - Hardiyanti Arhas, Sitti; Mirdayani, Mirdayani; Niswaty, Risma; Suprianto, Suprianto (Universitas Negeri Makassar, 2023)
Student understanding has a big role in the learning process to achieve the learning goals themselves. Therefore, research has a significant role in identifying factors that influence student understanding. This research discusses the influence of the use of learning media on the understanding of Office Administration Education students, at the Faculty of Social Sciences and Law, Universitas Negeri Makassar. This type of research is descriptive research with a quantitative approach. The sample used in this research was 88 students with a population of 175 students. This research presents newer information by linking detailed theories and different loci to previous research so that it can be used as evaluation material to improve student understanding through several indicators in the use of learning media. The results of the research show that the indicators used for each variable show that the use of learning media is in the good category and the understanding variable is in the very high category. Based on the correlation test, there is a relationship between the two variables. So it can be concluded that there is a positive and significant influence of learning media on the understanding of Office Administration Education students, Faculty of Social Sciences and Law, Universitas Negeri Makassar.